Performance evaluation index for Islamic banks based on Maqasid al-Shariah - Islam, Rafikul; Mohamed, Mustafa Omar; Tarique, Kazi Md.; Radzuan, Ummi Nasyrah; Abdul Razak, Dzuljastri; Hamdan, Hamdino (2018)
The upsurge of Islamic banking has always been seen from the perspective of growth of assets and market share which somehow depict the profit oriented nature of a business entity. “Riba free banking” seems to be the only factor that differentiates Islamic banking from its conventional counterpart. As a result, the true objective of Islamic banking which is the fulfillment of “Maqasid al-Shari’ah” (Objective of Islamic law) have not been formally addressed. Currently, Islamic banks are being evaluated using the same conventional standards of other banks which mainly focus on financial measures. Hence, a paradigm shift is required in the Islamic banking industry where the framework of Maqasid al- Shari’ah is used for performance evaluation. The objective of this study is to develop a Maqasid al-Shari’ah based index by operationalising the Maqasid framework that combines the Maqasid theories of Imam al Ghazali and Abu Zaharah. At first, semi-structured interviews of 12 experts on Islamic banking and finance (IBF) were conducted to select the variables for indexing. Afterwards, a focus group discussion was arranged consisting five experts in IBF to validate the selected variables. Then, an analytic hierarchy process (AHP) is employed to determine the relative importance and weight of each Maqasid item and sub-items. The respondents in this case are industry experts, Shari’ah scholars, Shari’ah committee members and academics. Based upon this, an index is developed. Afterwards, the index is tested on 11 selected sample banks in Malaysia and Bangladesh. The result reveals that RHB Islamic bank rank top among the selected Islamic banks. This study contributes to the theory of Maqasid al-Shari’ah with respect to banking performance evaluation by identifying the necessary variables to operationalize Maqasid items. The Maqasid-based index is expected to assist stakeholders to measure how far the performance of Islamic banks are in line with the Maqasid al-Shari’ah.